The apple of his eye: converts from Islam in the reign of Louis IX - Jordan, William C. (Jews, Christians, and Muslims from the Ancient to the Modern World Ser., 2019)
Cover -- Title Page -- Copyright Page -- CONTENTS -- List of Illustrations -- Acknowledgments -- Technical Matters -- INTRODUCTION: Converting the World -- CHAPTER 1 The Crusade of 1248-1254 -- CHAPTER 2 The Resettlement of the Converts -- CHAPTER 3 Living in France -- EPILOGUE: The Last Crusade -- References -- Index.